Current advances in the detection of COVID-19 and evaluation of the humoral response. Issue 2 (7th January 2021) - Huergo, Maria Ana Cristina; Thanh, Nguyen Thi Kim
Abstract : SARS-CoV-2 and humoral response determinations to understand and control the spread of COVID-19. Abstract : The new outbreak caused by coronavirus SARS-CoV-2 started at the end of 2019 and was declared a pandemic in March 2020. Since then, several diagnostic approaches have been re-adapted, and also improved from the previous detections of SARS and MERS coronavirus. The best strategy to handle this situation seems to rely on a triad of detection methods: (i) highly sensitive and specific techniques as the gold standard method, (ii) easier and faster point of care tests accessible for large population screening, and (iii) serology assays to complement the direct detection and to use for surveillance. In this study, we assessed the techniques and tests described in the literature, their advantages and disadvantages, and the interpretation of the results. Quantitative reverse transcription polymerase chain reaction (RT-qPCR) is undoubtedly the gold standard technique utilized not only for diagnostics, but also as a standard for comparison and validation of newer approaches. Other nucleic acid amplification methods have been shown to be adequate as point of care (POC) diagnostic tests with similar performance as RT-qPCR. The analysis of seroconversion with immunotests shows the complexity of the immune response to COVID-19. The detection of anti-SARS-CoV-2 antibodies can also help to detect previously infected asymptomatic individuals with negative RT-qPCR tests. Nevertheless, more controlled serology cohort studies should be performed as soon as possible to understand the immune response to SARS-CoV-2.